Approaches and results of intersectoral actions for tuberculosis control in the world: A scoping review - Rosiane Davina da Silva; Erica Rayane Galvão de Farias; José Mateus Bezerra da Graça; Eslia Maria Nunes Pinheiro; Elisângela Franco de Oliveira Cavalcante (PLoS ONE, 2025)
Background Tuberculosis is a neglected disease with a wide global scope that overcomes public health challenges, also constituting an obstacle to social development. In the effort to control the disease, Tuberculosis Control Programs around the world have aligned their actions with the World Health Organization End TB Strategy, which emphasizes intersectorality as a fundamental component for effective disease control. Objective To map the approaches and results of intersectoral tuberculosis control actions at the global scenario. Methodology This scoping review followed the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines and the Joanna Briggs Institute manual, ensuring methodological rigor and transparency. The review protocol was registered in the Open Science Framework. Searches were carried out in indexed databases and in the gray literature. Data collection took place by two independent reviewers, with results stored and organized in spreadsheets. Results Three hundred and ninety-six (396) studies were identified, of which 60 were analyzed in full, resulting in the inclusion of 11 studies for the final review. It was evidenced that intersectoral articulation is fundamental in tuberculosis control, involving sectors such as health, education, social assistance and justice, to ensure adequate health care and social support, particularly for vulnerable populations. Community education and awareness played a central role in treatment adherence and reducing stigma, while resource mobilization was needed to maintain health services, especially in contexts of scarcity. Conclusion The integration of intersectoral services, involvement of non-governmental organizations and active community participation are essential elements for effective tuberculosis control. The findings reinforce the importance of addressing the social determinants of health to achieve the objectives of the End TB strategy, promoting an environment conducive to the prevention, early detection and effective treatment of the disease.